Revealing The Impact Of Regional Government Function Budget Patterns On Achievements SDG 11 In Indonesia - Novitasari, Rahmi Dwi; Sugianto, Sugianto (LPPM ISNJ Bengkalis, 2024)
This study aims to analyze the influence and effectiveness of local government budget allocations on nine main functions in achieving SDG 11 in Indonesia, focusing on decent and affordable housing. This study uses a quantitative method with 1,424 observations from 356 provinces/districts/cities during 2019–2023 through propositional sampling techniques, and it was analyzed using individual regression. The study results indicate variations in the influence of budget allocations on achieving SDG 11. The budget for public services, housing and public facilities, tourism, and culture negatively affect SDG 11. In contrast, the budget for the environment and education positively affects SDG 11, while the budget for the economy, health, and social protection does not show an effect. Control variables, such as government age and status, positively affect, while geographical location has no effect. The theoretical implications of this study strengthen the theory that appropriate budget allocation can improve access to decent housing, clean water, and sanitation. Practically, this study guides local governments in formulating more effective budget allocation policies to support social development and the achievement of SDG 11 in a sustainable manner.